the adventures of huckleberry finn: philippine edition - Twain, Mark; Mark twain (philippine Heninle cengage learning, 2010)
Huckleberry Finn escapes from his evil, drunken father who isa trying to steal his treasure. Huck bestfriends jim, a runaway slave and together they float towards freedom on a raft down the Mississppi rivers. they encounter thieves and murderers, con men and husksters as they journey together. Mark twain's timeless tale of friendship and adventure shows us a boy coming of age and learning about life's pains and pleasures!
English